Fruiting Phenology of the Golden Langur (Trachypithecus geei) Food Plants at Chakrashila Wildlife Sanctuary, Kokrajhar, BTR, Assam - Brahma, Sanjib; Brahma, Jayeeta (Indian Forester, 2025)
The conservation of plants and animals is one of the biggest challenges facing today in Bodoland Territorial Region (BTR) of Assam. A large scale encroachment of forest land, practising of monotonous crop like tea and rubber in and around Chakrashila Wildlife Sanctuary hampers the golden langur food plant diversity and its availability. People around the sanctuary have less awareness on the importance of forest cover and golden langur food plants. The present study comprises 17 species of the golden langur food plants from 12 different families. Studies were done on 15 numbers of individual samples from 17 numbers of species. Altogether 255 numbers of individual plants were identified through transect method inside the sanctuary. The data of fruiting status were collected in 30 days interval for all individual plant samples. The result of this study gives some of the vital information regarding the diversity and availability of the golden langur food plants at Chakrashila Wildlife Sanctuary. The result tells about the fruiting season, duration of fruiting, peak of fruiting season and scarcity of fruiting. Based on the fruiting status the studied golden langur food plants are categorised as summer & pre-monsoon fruiting as well as Monsoon & post-monsoon fruiting.